Analysis of Information System Development in the Context of the Latest Technological Era: Challenges and Potential for Success - Adi Nugroho Susanto Putro; Sabil Mokodenseho; Adit Mohammad Aziz (Westscience Press, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are integral to economic growth, and in the current technological era, information system development has become crucial for their success. This research explores the challenges faced by MSMEs in West Java regarding information system development and examines the potential impact on business performance. Through mixed-methods research involving literature review, case studies, and surveys, the study reveals that financial constraints, lack of expertise, resistance to change, integration issues, and cybersecurity concerns hinder information system adoption. However, successful integration leads to improved efficiency, customer engagement, and innovation. The findings offer strategic insights for fostering MSME growth through technology in West Java.